Comparison between optical microscopy and automation for cytometric analysis of pericardial fluids in a cohort of adult subjects undergoing cardiac surgery - Buoro, Sabrina; Seghezzi, Michela; Baigorria Vaca, Maria del Carmen; Manenti, Barbara; Moioli, Valentina; Previtali, Giulia; Simon, Caterina; Cugola, Diego; Brucato, Antonio; Ottomano, Cosimo; Lippi, Giuseppe (Journal of clinical pathology, 2019)
AimsLimited information is available on number and type of cells present in the pericardial fluid (PF). Current evidence and has been garnered with inaccurate application of guidelines for analysis of body fluids. This study was aimed at investigating the performance of automate cytometric analysis of PF in adult subjects.MethodsSeventy-four consecutive PF samples were analysed with Sysmex XN with a module for body fluid analysis (XN-BF) and optical microscopy (OM). The study also encompassed the assessment of limit of blank, limit of detection and limit of quantitation (LoQ), imprecision, carryover and linearity of XN-BF module.ResultsXN-BF parameters were compared with OM for the following cell classes: total cells (TC), leucocytes (white blood cell [WBC]), polymorphonuclear (PMN) and mononuclear (MN) cells. The relative bias were −4.5%, 71.2%, 108.2% and −47.7%, respectively. Passing and Bablok regression yielded slope comprised between 0.06 for MN and 5.8 for PMN, and intercept between 0.7 for PMN and 220.3 for MN. LoQ was comprised between 3.8×106 and 6.0×106 cells/L for WBC and PMN. Linearity was acceptable and carryover negligible.ConclusionsPF has a specific cellular composition. Overall, automated cell counting can only be suggested for total number of cells, whereas OM seems still the most reliable option for cell differentiation.